Biocompatible Quantum Dots for Biological Applications - Rosenthal, Sandra J. (2011)
Semiconductor quantum dots are quickly becoming a critical diagnostic tool for discerning cellular function at the molecular level. Their high brightness, long-lasting, sizetunable, and narrow luminescence set them apart from conventional fluorescence dyes. Quantum dots are being developed for a variety of biologically oriented applications, including fluorescent assays for drug discovery, disease detection, single protein tracking, and intracellular reporting. This review introduces the science behind quantum dots and describes how they are made biologically compatible. Several applications are also included, illustrating strategies toward target specificity, and are followed by a discussion on the limitations of quantum dot approaches. The article is concluded with a look at the future direction of quantum dots.